Pengembangan Instrumen Penilaian Teks Deskripsi Berbasis HOTS Berbantuan Aplikasi Quizizz di Kelas VII SMP Amalia Medan - Mariani, Titin; M. Hutagalung, Surya; Adisaputera, Abdurahman (Jurnal Bahastra, 2025)
This study develops a Higher Order Thinking Skills (HOTS)-based assessment instrument for descriptive texts using Quizizz for seventh-grade students at SMP Amalia Medan. The research employs Sugiyono’s (2015) RD method, implementing seven stages: problem identification, data collection, product design, validation, revision, testing, and final revision. Validation by three experts yielded a 94% validity rate, confirming strong instrument reliability. Of 30 developed questions, 25 were valid (r 0.3291) with a reliability coefficient of 0.78 ( 0.60). The difficulty level was "Moderate", and two questions with low discriminative power were removed. Most distractors were effective, with over 5% of students selecting alternative answers. Trial results indicated students' HOTS levels were categorized as "Good", demonstrating the instrument's effectiveness in evaluating higher-order thinking in descriptive text comprehension. This study highlights the potential of Quizizz as an engaging digital tool for HOTS-based assessments.